Adat and Islamic concept of incest in literary works on Minangkabau society: a problem of ideology - Umar Junus, (Universiti Kebangsaan Malaysia, 2002)
There are four types of the incestuous relation: marital or extramarital, possible or manifest, intergeneration or intrageneration, against the Islamic or against the adat principle. As extramarital and an intergeneration relationship is only found in one work, it is then not an important topic in literary works on Minangkabau society. This is also applicable to incestuous marriage which is against the adat principle. The most frequent incestuous relation found in literary works on Minangkabau society is the (possible) incestuous marriage between a half-brother and a half-sister which is against the Islamic principle – the incestuous marriage between a brother and a sister is against both the Islamic and the adat principle and it is only found in one work. Despite the popular belief that there is a confrontation between the adat and the Islamic principles in Minangkabau culture, a couple only realize they have committed an incestuous marriage after re-establishing their contacts with their relatives in their village, which is the realm of adat. It is only discovered through the cooperation of an adat mechanism